Business Communication : Building Critical Skills Sixth Edition - Kitty O. Locker (McGraw Hill Irwin, 2014)
Business Communication: Building Critical Skills was built to provide the ultimate in freedom, flexibility, and focused classroom. Broken into 30 modular chapters, this text provides topic-focused modules, allowing instructors to customize their resources piece-by-piece to best suite their course and teaching style. Each module has a strong workplace activity orientation, supporting students to build critical skills in writing, speaking, and listening. Locker/Kaczmarek is grounded in solid business communication fundamentals, and supports students to piece together what is needed to be a successful communicator for the 21st century